1991
DOI: 10.1128/mcb.11.9.4314
|View full text |Cite
|
Sign up to set email alerts
|

Liver cells contain constitutive DNase I-hypersensitive sites at the xenobiotic response elements 1 and 2 (XRE1 and -2) of the rat cytochrome P-450IA1 gene and a constitutive, nuclear XRE-binding factor that is distinct from the dioxin receptor.

Abstract: Dioxin stimulates transcription from the cytochrome P-450IA1 promoter by interaction with the intracellular dioxin receptor. Upon binding of ligand, the receptor is converted to a form which specifically interacts in vitro with two dioxin-responsive positive control elements located in close proximity to each other about 1 kb upstream of the rat cytochrome P-450IA1 gene transcription start point. In rat liver, the cytochrome P-450IA1 gene is marked at the chromatin level by two DNase I-hypersensitive sites tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…At the cyplal promoter, TCDD induces (via the Ah receptor) a rapid and actinomycin D-insensitive change in chromatin structure and nucleosome positioning that is temporally associated with the onset of transcription. This change is consistent with the observation of an inducible DNase I-hypersensitive site at the cyplal transcriptional promoter in rat liver (24).…”
Section: Itors Of Transcriptional Initiation (19-21)supporting
confidence: 91%
“…At the cyplal promoter, TCDD induces (via the Ah receptor) a rapid and actinomycin D-insensitive change in chromatin structure and nucleosome positioning that is temporally associated with the onset of transcription. This change is consistent with the observation of an inducible DNase I-hypersensitive site at the cyplal transcriptional promoter in rat liver (24).…”
Section: Itors Of Transcriptional Initiation (19-21)supporting
confidence: 91%
“…3) Gel retardation analyses reveal that uninduced cells contain proteins that bind to naked enhancer DNA in vitro; the structure and possible function of these proteins are unknown (21,23,39,40). Our analyses reveal no evidence for the corresponding protein-DNA interactions at the inactive enhancer in vivo.…”
Section: Discussionmentioning
confidence: 69%
“…1) The paucity of protein-DNA interactions suggests that the inactive enhancer is relatively inaccessible to DNA-binding proteins. For example, mouse hepatoma cells constitutively express a protein(s) at binds to naked, G-rich DNA in vitro (39). However, such binding does not occur at the CYPIAI promoter in vivo, unless the gene has been activated by TCDD.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro footprinting and gel shift experiments have also shown that, subsequent to binding aryl hydrocarbons, the AH receptor is activated to a form that binds specifically to XREs (12)(13)(14)(15)(16)(17). Information regarding the in vivo DNA-protein interactions important in regulating CYPlAl transcription has been provided through both lowresolution studies, employing DNase I (18), exonuclease mII (19), and restriction enzymes (20), and, recently, through highresolution in vivo footprinting studies (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%